Sustainable freshwater fisheries in Bangladesh: problems and pathways forward - Swarna, Sanzida R.; Ali, Md. Yeakub; Galib, Shams M. (Journal of Fisheries, 2026)
Bangladesh is one of the leading countries in global fish production; however, numerous problems and challenges persist. This paper summarises the problems faced by seven major stakeholder groups in the country’s fisheries sector: (i) fish farmers, (ii) freshwater fishermen, (iii) fish traders, (iv) fish seed producers, (v) fisheries administrators and extension personnel, (vi) researchers and (vii) fish consumers. Fish farmers reported 19 problems, with transportation issues being the most common (35% of respondents), followed by the lack of quality fish seed (20%). Freshwater fishermen reported 13 problems, with reduced fish catch as the most common (65%), followed by the shrinkage of fishing habitats (15%). For freshwater fish traders, lack of preservation and storage facilities was the most common problem, reported by 80% of respondents. Seven problems were reported by finfish seed producers; among the top-ranked, lack of quality brood and its high price were most common, reported by 60% and 40% of respondents respectively. Fisheries administrators and extension personnel reported nine problems, with insufficient manpower being the most common, reported by 70%. Eleven problems were reported by fisheries researchers, with inadequate research funding as the most common, reported by 60%. Fish consumers reported five problems, including price hikes and insufficient supply of native fishes. The results of this study will be useful in prioritising problems and formulating effective policies for the sustainable development of the fisheries sector in Bangladesh and other countries facing similar challenges.